Straszliwe boginie - Gruszewska, Joanna (Studia religiologica, 2015)
Recenzja: Małgorzata Oleszkiewicz-Peralba, Fierce Feminine Divinities of Eurasia and Latin America: Baba Yaga, Kālī, Pombagira and Santa Muerte, wydawnictwo Palgrave Macmillan 2015, s. 188